Fundamentals of heat and mass transfer - Incropera, Frank P. (John Wiley, 2007)
Introduction -- Introduction to conduction -- One-dimensional, steady-state conduction -- Two-dimensional, steady-state conduction -- Transient conduction -- Introduction to convection -- Externakl flow -- Internal flow --Free convection -- Boiling and condensation -- Heat exchangers -- Radiation: processes and properties -- Radiation exchange between surfaces -- Diffusion mass transfer.